Mimese e realidade em O ano da morte de Ricardo Reis - Prevedello, Tatiana (2006)
The object of study is the book O ano da morte de Ricardo Reis, written by José Saramago, in which he articulates the imprecise limits between historical discourse and literary criation, looking for a sense in the reality representation, that strenghtens in an inter-discoursing and inter-textual based upon the truth of history and the truth of fiction . Mimesis, consequently, constructs itself as a representational activity that does not reflect the real world, but (un)realizes it from fictional theme. When involving man s artistic manifestation, it designates the creative exercise, corresponding to a way to represent the world. It was intended to investigate and interpret mimesis in the book, studying the relationship between the fictional world and the Portugal social-historical reality, specifically Lisbon in 1936. It was possible noticing that the character Ricardo Reis in (dis)sacralized from his poetic aura that surrounded the Fernando Pessoa heteronimous, when directly confronted with hostility of a world terrified by authoritarian regimes that ruled before the Second World War. In the text plan, the process of pre-configuration, configuration and reconfiguration of space and time, indicates that the past reality is present in the narrative, involving the character Ricardo Reis experiencing the labyrinths suggested from the Lisbon city, taken from the book The god of the labyrinth, and from news reported in the press. On this perspective, the book O ano da morte de Ricardo Reis has an interlocutor attitude towards historical reality , not restricted to a simple representation of past events in Portugal.